Modulation of bacterial ghosts – induced nitric oxide production in macrophages by bacterial ghost‐delivered resveratrol. (31st January 2013) - Koller, Verena J.; Dirsch, Verena M.; Beres, Hortenzia; Donath, Oliver; Reznicek, Gottfried; Lubitz, Werner; Kudela, Pavol
<x xml:space="preserve">Abstract</x> The present study aimed to investigate the capacity of resveratrol (RV) delivered into macrophages by bacterial ghosts (BGs), representing intact empty nonliving envelopes of Gram‐negative bacteria, to modulate nitric oxide (NO) production related to the presence of the pathogen‐associated molecular patterns on the surface of BGs. Incubation of the murine macrophage cell line RAW 264.7 with BGs leads to a dose‐dependent activation of inducible NO synthase. To modify BG‐induced NO formation in RAW 264.7 cells by RV; BGs were loaded with RV (RV‐BGs) and incubated with murine macrophages in a dose‐dependent manner. RV‐BGs delivering RV to the target macrophages significantly reduced BG‐induced NO production with concentration of RV more than one order of magnitude lower than the amount of RV capable of reducing NO formation when applied directly. Moreover, no cytotoxic impact of BGs on the viability of RAW 264.7 cells added to macrophages alone or loaded with RV was detected after a mutual 24 h incubation, whereas cell viability slightly decreased ( 10%) when RV concentrations of 30 μm alone were applied. The results obtained in the present study clearly indicate that the intracellular delivery of RV by BGs significantly enhances the total RV effect.